‘What if technology worked in harmony with nature?’: imagining climate change through Prius advertisements - Seufert, Juergen H. (Taylor & Francis, 2016)
[Review of article with same title by Garland, J., Huising, R., and Struben, J. In: Organization, 2013, 20 (5), pp. 679–704]